Alexander the Great in comics: notes on Classical Reception and History Teaching - Pelegrín-Campo, Julián (Clio. History and History Teaching, 2019)
The presence of Alexander the Great in comics has been virtually ignored by the reception studies both about Classical Antiquity and about the Macedonian conqueror, and very sparsely analysed by the research about the treatment of Antiquity in comic books. However, the existence of more than two hundred works published over almost a century with graphic representations of Alexander shapes a corpus with more than enough value to be recognized as object of study by academic research because of the educational possibilities of the most recent historical-biographical approaches from History teaching, and the importance of Alexander the Great as a reference icon in the contemporary popular culture.
Keywords: Alexander the Great; comic; classical reception; History teaching; contemporary popular culture